Penerapan Metode Active debate dalam Meningkatkan Keterampilan Berbicara pada Mata Pelajaran Bahasa Indonesia - Zulyetti, Zulyetti (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2014)
This research aims at understanding factual depiction regarding implementation of learning method of active debate in improving speaking skills on the subject of Bahasa Indonesia at the sixth grade of Primary School 2 of Klieng, Aceh Besar Regency in 2012/ 2013 School Year. The research uses two cycles of the action research which are each cycle consists of four stages such as : planning, acting and observing, reflecting and revising. The object of the research is the 30 pupils of sixth grade of Primary School 2 of Kling, Aceh Besar Regency, Province of Aceh. The data collected here are test result, observation sheet of learning processes. In the first cycle the achieved average score was 6.57, as in the second cycle the average score climed to 7.57, and experienced an increasing again in third cycle on 8.33 score. Except the average score, the students activity also experienced elevating quality such as asking question at first cycle agregates 16.67 percent, then 10 percent at the second cycle, and 25 percent at the third cycle. Whereas responsing of clasmates askings, at the fist cycle agregates 21.67 percent, then 13.34 percent at the second cycle, and 18.43 at the third cycle. Furthemore aspect of paying attention on teacher explanation at the first cycle agregates 71.67 percent, then 85 percent at the second cycle, and finally 96.67 percent at the third cycle. While, aspect of discussion at the first cycle agregates 81.67 percent, then 86.67 percent at the second cycle, and 100 percent at the third cycle.